Peningkatan green human resource management melalui green organizational commitment dan knowledge sharing - Ilham Wijaya Bima Unnas; Dwiarko Nugrohoseno (Universitas Negeri Surabaya, 2026)
Climate change and environmental sustainability issues encourage organizations to integrate environmentally friendly principles into their management practices. This study aims to examine the effect of green human resource management on green innovation behavior through green organizational commitment, as well as to test the moderating role of knowledge sharing. A quantitative approach was employed by collecting data through questionnaires from 100 employees of PT Surabaya Industrial Estate Rungkut. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS version 4.1.1.6. The results indicate that green human resource management has a positive and significant effect on green innovation behavior and green organizational commitment. Furthermore, green organizational commitment significantly mediates the relationship between green human resource management and green innovation behavior. However, knowledge sharing does not significantly moderate the relationship between green organizational commitment and green innovation behavior, nor the indirect effect in the mediation model. These findings suggest that green innovation behavior is primarily driven by employees’ environmental commitment and organizational sustainability policies rather than the intensity of knowledge exchange among employees